Practicing Mortality - Dustin, C. author. aut Link
XV, 253 p.
Keywords: A collaborative undertaking between an artist and a philosopher, this monograph attempts to deepen our understanding of 'contemplative seeing' by addressing the works of Plato, Thoreau, Heidegger, and more. The authors explore what it means to 'see' reality and contemplate how viewing reality philosophically and artfully is a form of spirituality. In this way, by developing a new conception of active visual engagement, the authors propose a way of seeing that unites both critical scrutiny and spiritual involvement, as opposed to simple passive reception.